Work Stress, Health Status and Presenteeism in Relation to Task Performance Among Chinese Medical Staff During COVID-19 Pandemic - Jia, Huanhuan; Shang, Panpan; Gao, Shang; Cao, Peng; Yu, Jianxing; Yu, Xihe (Frontiers in Public Health, 2022)
Objective: The performance of medical staff is of great importance to the quality of medical services, and it has been a concern for a long time. In the context of increasing demand for medical services, a cross-sectional study was conducted among medical staff in Jilin Province, Northeast China, to explore the effects of work stress, health status and presenteeism on task performance. Methods: The Challenge and Hindrance-Related Self-Reported Stress scale, Short Form-8 Health Survey scale, Stanford Presenteeism Scale and Task Performance Scale were adopted to assess the work stress, health status, presenteeism and task performance. Descriptive analysis, t test, one-way analysis of variance (ANOVA), correlation analysis and structural equation modeling (SEM) were applied to analyze the data. Results: 4347 questionnaires were distributed, and 4261 were valid, for an effective rate of 98.02%. The mean scores for work stress, health status, presenteeism and task performance were 2.05±0.84, 4.18±0.68, 2.15±0.79 and 4.49±0.64, respectively. The ANOVA results showed that there were significant differences in the task performance scores between different genders, ages, marital statuses, professional titles, departments and work years (P<0.05). Work stress (β=-0.136, P<0.001) and presenteeism (β=-0.171, P<0.001) were negatively correlated with task performance, and health status (β=0.10; P<0.001) was positively correlated with task performance. Health status (β=-0.070; P<-0.001) and presenteeism (β=-0.064; P<0.001) mediated the relationship between work stress and task performance (P<0.001). Presenteeism mediated the relationship between health status and task performance (β=0.07; P<0.001). Conclusion: The study proposes that the greater that work stress is, the more serious that presenteeism is, and the worse that task performance is; the better that health status is, the better that task performance is. At the same time, health status and presenteeism play intermediary roles between work stress and task performance, and presenteeism plays an intermediary role between health status and task performance.